Organic Removal Treatment Using Microbubble Generator (MBG) in Eutrophic Disorder Condition - Tri Yulianti; Sri Puji Saraswati; Johan Syafri Mahathir Ahmad; Wiratni Budhijanto (Journal of the Civil Engineering Forum, 2021)
The Techno Park basin, built as an extension of a small tributary of the Code River primarily acts as a retention basin for runoff during the rainy season. It improves the quality of water that has been degraded by domestic wastewater discharge from the surrounding community. Therefore, this study aims to assess the extent to which water quality of the basin can be improved with aeration technology. The aeration technology is a Microbubble Generator (MBG) built using a 100 Watts submersible pump with three horizontal nozzles at a depth of 40 cm from the water surface. Furthermore, the profiles of dissolved oxygen (DO) concentration were measured at the basin’s inlet and outlet, as well as the depths of 1 m below surface water and the bottom of the basin. Diurnal DO was measured to investigate the causes of supersaturation. The aeration performance was also determined from the COD parameters at the inlet and outlet. Discharge measurements were then conducted on the tributary/drainage channel to the inlet basin. The result showed that the DO supersaturation concentration has been attributed to the contribution of photosynthesis from phytoplankton such as algae. Furthermore, no change in DO concentration was observed in a range of 1 m depth from the surface of the water to the bottom (0.3 - 0.14 mg-DO/l). In this eutrophic state, DO increased exponentially during the daytime hours and then decreased during the night. The daily measurement showed an increase in the average DO of 2.31 mg/l (standard deviation of 1.56 mg/l), with average CODinlet fluctuations of 18.79 mg/l (standard deviation of 13.56 mg/l) and average CODoutlet of 14.38 mg/l (standard deviation 2.94 mg/l). Due to additional DO concentration coming from eutrophication during daylight, it was not possible to make a precise assessment of the effectiveness of the MBG aerator.